Degradable iron skeleton reinforced Zn / Fe / Mg composite material and preparation method and application thereof

By introducing iron foam brackets and magnesium powder into zinc alloy materials and using cumulative stacking and rolling technology, a degradable iron frame-enhanced Zn/Fe/Mg composite material with high strength and significant work hardening capabilities was prepared, which solved the problem of insufficient mechanical properties of zinc alloy materials and met the mechanical and corrosion performance requirements of bone implants.

CN119609115AActive Publication Date: 2025-03-14XIANGTAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411888446.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-14
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing zinc alloy materials have shortcomings in mechanical properties, especially the problem of insufficient processing softening and hardening capabilities, which are difficult to meet the mechanical and corrosion performance requirements of bone implants.

Method used

By mixing zinc powder and magnesium powder in a certain proportion and filling the iron foam bracket, and using the cumulative stacking process, a degradable iron frame-reinforced Zn/Fe/Mg composite material with Zn, Fe, Mg three-phase matrix and binary phase diffusion was prepared. This method uses the galvanic corrosion characteristics of the iron bracket to improve corrosion resistance, while the Zn phase, Fe and Mg phases work together to improve strength and work hardening capabilities.

Benefits of technology

The prepared composite materials exhibit high strength, appropriate corrosion resistance and significant work hardening capabilities, which can meet the mechanical and corrosion requirements of bone fixation implants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119609115A_ABST
    Figure CN119609115A_ABST
Patent Text Reader

Abstract

The invention discloses a degradable iron framework reinforced Zn / Fe / Mg composite material and a preparation method and application thereof.The preparation method comprises the steps that magnesium powder and zinc powder are mixed to obtain mixed powder, iron foam is filled with the mixed powder, then the iron foam is covered with two Zn plates up and down to obtain a composite plate, the composite plate is subjected to single-pass cold rolling to obtain a cold-rolled plate, and the cold-rolled plate is subjected to hot rolling to obtain the degradable iron framework reinforced Zn / Fe / Mg composite material. And cutting the cold-rolled sheet into two pieces from the middle, laminating, then carrying out single-pass cold rolling, and repeating cutting, laminating and single-pass cold rolling to finally obtain the degradable Zn / Fe / Mg layered composite material. The degradable Zn / Fe / Mg composite material prepared by the invention shows obvious work hardening capacity at room temperature, the strength of the degradable Zn / Fe / Mg composite material is improved by 260% compared with the strength of the same pass of pure zinc plate rolling, and the degradable Zn / Fe / Mg composite material has excellent mechanical properties and anti-tumor properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biodegradable zinc alloy composite materials, and in particular relates to a degradable iron skeleton reinforced Zn / Fe / Mg composite material and a preparation method and application thereof. Background Art

[0002] At present, biodegradable biomedical metal materials are mainly divided into magnesium-based, iron-based and zinc-based biodegradable metals. Compared with the shortcomings of most magnesium-based alloys that degrade too quickly and iron-based alloys that degrade too slowly, the corrosion rate of zinc and its alloys is between the two. It has a moderate degradation rate, and zinc and its alloys have good biocompatibility. Therefore, zinc and its alloys are considered to be the most promising biodegradable bone implant materials. However, since the mechanical properties of pure zinc are not sufficient to meet the use as medical implants, zinc alloy biodegradable biomaterials are mainly treated by adding alloying elements, rapid solidification, heat treatment, and deformation, etc., on the basis of meeting biocompatibility and degradation performance, to effectively improve the mechanical properties of zinc alloys.

[0003] The ARB technology was first proposed by Japanese scholar Professor YSaito in 1998, and the technology was successfully applied to pure aluminum, aluminum alloys, interstitial free (IF) steel and a small amount of deformed magnesium alloys. Since then, the ARB process has been developed and promoted for the preparation of ultrafine-grained or nanocrystalline metal layered composite materials. The principle of the ARB process: First, the metal sheets of the same size are surface treated to remove the attached oil and surface oxide layer to facilitate the good bonding of dissimilar metals. Then, the initial metals are cross-stacked together in an ABABA manner and rolled at room temperature or below the recrystallization temperature. Under the action of a reduction of more than 50%, rolling force and friction, the stacked sheets are rolled into a whole, and then the rolled sheets are cut into the same size. The same process is repeated and the ARB is repeated. The cumulative strain can reach a large value, and a large reduction can be obtained in theory. This process breaks through the limitation of the traditional rolling reduction and can continuously prepare metal layered composite sheets with ultrafine grain structure. ARB is a rolling process with interface bonding, continuous solid phase diffusion, and continuous strain generation and accumulation. During the cumulative rolling process, the cumulative strain continues to increase, and the resulting mechanical alloying effect not only improves the bonding ability between heterogeneous interfaces, but also refines the grains of the component metal layers, thereby improving the mechanical properties of the material and improving plastic deformation. Compared with other SPD processes, ARB technology has its own outstanding advantages, mainly manifested in: low cost and simple process. Only through ARB modification without adding alloying elements, high strength is obtained, and it has a strength comparable to that of highly alloyed alloys. This process has great advantages in reducing production costs and material density and improving the recycling performance of metal materials. In addition, this process does not require special equipment. Since rolling welding has been widely used in metal cladding production, it has high productivity, can produce large-sized materials, and is easy to realize industrial production. Therefore, the cumulative rolling process has become the most potential application process in the field of preparing high-strength, high-toughness, and lightweight ultrafine-grained metal layered composite materials.

[0004] Magnesium (Mg) is one of the essential elements for the human body. It is also one of the elements with a high content of metal elements in the human body. It has many extremely important physiological and biochemical effects. It exists in various tissues in the body and participates in many biological processes. More than 60% of the magnesium in the human body is distributed in bones and teeth, forming a complex with the protein in the bones to promote the phosphorylation process of bones. Because magnesium is involved in the hydrolysis of adenosine triphosphate, magnesium is involved in almost all physiological activities of the human body. It is an important auxiliary factor in the metabolism of sugar and fat nutrients, and maintains the transmission and normal activity of muscles and nerves. At the same time, magnesium has an inhibitory effect on the central nervous system, thereby playing a sedative role, acting on the surrounding blood vessels, which is conducive to promoting vasodilation and achieving the effect of lowering blood pressure. In addition, adding magnesium to the zinc matrix can improve the cell compatibility of zinc.

[0005] With the in-depth study of zinc alloys, the shortcomings of zinc alloy mechanical properties have also emerged, that is, most of the current zinc alloys show work-softening behavior or insufficient work-hardening ability, and there is also an aging (self-ageing) phenomenon (that is, the plasticity of the alloy will be greatly reduced with the extension of room temperature storage time), which has become the biggest challenge faced by zinc alloys in clinical applications. The problem of insufficient work-softening and work-hardening ability of zinc alloys is related to the low melting point of zinc. However, heterogeneous structural materials have a unique combination of strength and ductility, in which fine grains give material strength through the back stress strengthening mechanism, and coarse grains can provide the necessary work hardening and uniform elongation.

[0006] The mechanical and corrosion properties required of biodegradable metal materials depend on their intended use. Orthopedic bone fixation applications such as bone plates and screws need to maintain their mechanical integrity in the human body for 3-6 months. Specific mechanical and corrosion requirements for bone fixation implant biomaterials: the corrosion rate in simulated body fluid (SBF) at 37°C should be less than 500 μm / year, the strength should be greater than 200 MPa, and the elongation should be greater than 10%. Three biodegradable alloy systems are currently being widely studied: magnesium (Mg), iron (Fe), and zinc (Zn), as well as their alloys and composites. However, iron and its alloys degrade very slowly in physiological environments, although their corrosion products are usually not completely degraded in the body. The degradation rate of magnesium alloys in the human body is too fast. Zinc alloys have the most moderate degradation rate among the three biodegradable alloys because the standard electrode potential of zinc (0.763 V) is between magnesium (2.356 V) and iron (0.44 V). In addition, as one of the essential trace elements in the human body, zinc plays a key role in physiological functions, cell metabolism, and gene expression. In addition, zinc can promote bone tissue development and inhibit bone resorption, showing osteoinductive effects on bone tissue formation in vivo. Therefore, for biodegradable implant applications, Zn alloys are superior to Mg and Fe alloys in terms of degradation rate and biological function.

[0007] Therefore, considering the relatively slow corrosion rate of zinc alloys, the degradation rate of zinc-based composites can be increased by accelerating the anodic corrosion characteristics of galvanic corrosion, thereby meeting the degradation rate requirements of bone implants. Zinc / hydroxyapatite composites prepared by spark plasma sintering have improved biocompatibility and adjustable degradation rate by forming galvanic corrosion in a physiological environment. Due to their three-dimensional (3D) network structure, high porosity and large specific surface area, metal foams are commonly used in devices such as electrodes, catalysts, filters, thermal conductors and sound absorbers. By combining foam metal as a reinforcement phase and Zn alloy as a matrix, metal composites with a continuous network and a three-dimensional uniformly distributed reinforcement phase can be prepared. This has a completely different topological structure compared to traditional composites with randomly distributed reinforcement phases.

[0008] In summary, although there are reports in the prior art of obtaining zinc-based composite materials by laminated rolling, there has been no report so far on the introduction of an iron foam scaffold filled with powder to form a degradable Zn / Fe / Mg composite material with a Zn, Fe, and Mg three-phase matrix and a binary phase dispersion in the zinc alloy in terms of microstructure. Summary of the invention

[0009] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing a degradable iron skeleton reinforced Zn / Fe / Mg composite material having high strength, suitable corrosion resistance and significant work hardening ability. The preparation method of the present invention utilizes the three-dimensional structure and large specific surface area of ​​the foam metal, fills the iron foam with zinc powder and magnesium powder mixed in a certain proportion, and then adopts the cumulative rolling method to obtain the degradable iron skeleton reinforced Zn / Fe / Mg composite material. The network foam structure is responsible for providing more suitable corrosion resistance through galvanic corrosion; in addition, the Zn phase mainly contributes to ductility, while the Fe and Mg phases are responsible for enhancing strength and work hardening ability. The composite material prepared by the above preparation method exhibits metallurgical interface bonding, uniform reinforcement distribution and large-area galvanic corrosion. The composite material is a bone fixation implant with application prospects.

[0010] The second object of the present invention is to provide a degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared by the above preparation method, which has high strength, suitable corrosion resistance and significant work hardening ability.

[0011] The third object of the present invention is to provide an application of a degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared by the above preparation method.

[0012] In order to achieve the above object, the present invention adopts the following technical solution: The invention discloses a preparation method of a degradable iron skeleton reinforced Zn / Fe / Mg composite material. The method comprises the following steps: mixing zinc powder and magnesium powder to obtain a mixed powder, filling iron foam with the mixed powder, and then covering the iron foam with two Zn plates from top to bottom to obtain a composite plate, subjecting the composite plate to single-pass cold rolling to obtain a cold-rolled plate, cutting the cold-rolled plate into two pieces from the middle, stacking them, and then subjecting them to single-pass cold rolling, and repeating the cutting-stacking-single-pass cold rolling to finally obtain the degradable Zn / Fe / Mg layered composite material.

[0013] The preparation method of the present invention is to fill the iron foam with zinc powder and magnesium powder mixed in a certain proportion, and then cover the iron foam with two Zn plates to obtain a composite plate, wherein the Zn phase mainly contributes to ductility, while the Fe and Mg phases are responsible for enhancing strength and work hardening ability. Under the above synergy, the obtained composite material exhibits excellent work hardening ability, while achieving the complementarity of zinc alloy strength and plasticity; the iron foam support layer filled with zinc powder and magnesium powder is responsible for providing more suitable corrosion resistance through galvanic corrosion.

[0014] The inventors found that when filling iron foam, only by using the synergistic effect of zinc powder and magnesium powder can a degradable Zn / Fe / Mg layered composite material be obtained through laminated rolling. If only magnesium powder is used, the final prepared Zn / Fe / Mg composite material is characterized and found to have many holes and reduced tensile properties. If only zinc powder is used, the strength deteriorates.

[0015] In a preferred embodiment, the particle sizes of the zinc powder and the magnesium powder are both 20-40 μm, and the purity is ≥99.9%.

[0016] In the present invention, by controlling the particle size of Mg powder and Zn powder within the above range, the powder can be made to fill the iron foam evenly and stably. If the particle size is too small, it will be difficult to hang and leak powder. If it is too large, it will be easy for holes to be not filled. If the holes are not filled, the holes will become larger after rolling, which will reduce the performance of the layered composite material.

[0017] In actual operation, the zinc powder and magnesium powder are first stored in a vacuum environment for later use.

[0018] In a preferred embodiment, in the mixed powder, the mass ratio of zinc powder to magnesium powder is 1-5:1.

[0019] Further preferably, in the mixed powder, the weight ratio of zinc powder to magnesium powder is 2-4:1, preferably 4:1. In the present invention, the ratio of zinc powder to magnesium powder filled into the iron foam has a great influence on the final performance. When zinc powder to magnesium powder is 4:1, the performance of the obtained composite material is optimal. If there is too much zinc powder, the strength will be poor, and if there is too much magnesium powder, the plasticity will be poor.

[0020] In a preferred embodiment, the pore size of the Fe foam is 80-110 ppi. In the present invention, the pore size of the Fe foam is controlled within the above range so that the powder can evenly and stably fill the iron foam. If the pore size is too large or too small, it will cause difficulty in powder filling, resulting in the generation of pores, affecting the performance of the layered composite material.

[0021] Preferably, the purity of the Fe foam is ≥99.9%.

[0022] Preferably, the thickness of the Fe foam is 1.5-2.5 mm.

[0023] Preferably, the thickness of the Zn plate is 0.8-1.5 mm.

[0024] In a preferred embodiment, the length and width of the Zn plate are consistent with those of the iron foam.

[0025] In a preferred embodiment, the mass ratio of the Zn plate to the iron foam support is 6-10:1.

[0026] Further preferably, the mass ratio of the Zn plate to the iron foam support is 8-10:1.

[0027] By controlling the thickness of the Zn plate and the iron foam support and the mass ratio of the Zn plate and the iron foam support within the scope of the present invention, the Zn / Fe / Mg layered composite material can be successfully obtained through cumulative rolling. If the thickness is too large, the strength will deteriorate, and if the thickness is too small, the plasticity will be poor and the number of rolling times will be reduced, which will reduce the work hardening and also reduce the strength.

[0028] In the actual operation process of the present invention, before filling the powder, the iron foam is first pickled with an oxalic acid solution and immediately dried, the iron foam bracket is pickled with an oxalic acid solution and immediately dried, and then a round stainless steel brush with a wire diameter of 0.3 mm is used to grind the contact surface between the Zn plate and the iron foam in parallel to the rolling direction to remove surface oxides and impurities, and the polished Zn plate is placed in acetone for ultrasonic cleaning for 5 minutes to remove residual powder and other impurities.

[0029] In a preferred embodiment, the deformation of the composite plate in a single cold rolling process is 60%-70%.

[0030] The preferred solution is to cut the cold-rolled sheet into two pieces from the middle, stack them, and then perform single-pass cold rolling. In the process of repeated cutting-stacking-single-pass cold rolling, the deformation of any single-pass cold rolling is controlled to be 50%-60%.

[0031] The inventors found that the cold-rolled plate is cut into two pieces from the middle, stacked, and then subjected to a single-pass cold rolling, and the cutting-stacking-single-pass cold rolling is repeated. During the repeated process, the deformation of the composite plate in a single-pass cold rolling is controlled within the above-mentioned range. This can make the alloy plates tightly bonded while avoiding cracking, and the final degradable iron skeleton reinforced Zn / Fe / Mg composite material has the best performance.

[0032] In a preferred embodiment, the number of repeated cutting-lamination-single-pass cold rolling is 2-10 times, preferably 6-10 times.

[0033] The present invention also provides a degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared by the above preparation method.

[0034] In a preferred embodiment, the degradable iron skeleton reinforced Zn / Fe / Mg composite material is mainly composed of strip-shaped light gray zinc layers, dark gray leaf-shaped iron phases are alternately interspersed therein and have a layered distribution, and black small particle magnesium phases are dispersed therein.

[0035] The present invention also provides the application of the degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared by the above preparation method, and the degradable iron skeleton reinforced Zn / Fe / Mg composite material is used as a biodegradable implant material. At the same time, a new approach is provided for preparing a degradable Zn-based alloy with high strength, suitable corrosion resistance and significant work hardening ability.

[0036] Beneficial Effects The preparation method of the present invention is to fill the iron foam with zinc powder and magnesium powder mixed in a certain proportion, and then cover the iron foam with two Zn plates to obtain a composite plate, first perform a single pass cold rolling on the composite plate to obtain a cold-rolled plate, cut the rolled plate into two pieces from the middle, stack them, and then perform a single pass cold rolling, repeat the cutting-stacking-single pass cold rolling, and finally obtain a degradable iron skeleton reinforced Zn / Fe / Mg composite material. The above method forms a degradable iron skeleton reinforced Zn / Fe / Mg composite material with a Zn, Fe, and Mg three-phase matrix and binary phase dispersion in the microstructure of the zinc alloy. Among them, the iron support is responsible for providing more suitable corrosion resistance through galvanic corrosion; in addition, the Zn phase mainly contributes to ductility, while the Fe and Mg phases are responsible for enhancing strength and work hardening ability. The composite material exhibits metallurgical interface bonding, uniform reinforcement distribution and large-area galvanic corrosion, and the composite material is expected to have promising bone fixation implant applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0038] Figure 1 Schematic diagram of the preparation of cold-rolled sheet of degradable iron skeleton reinforced Zn / Fe / Mg composite material in the embodiment.

[0039] Figure 2 This is the XRD diagram of the degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared in the example after rolling 10 times.

[0040] Figure 3 The tensile stress-strain curve and corresponding tensile property data of the degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared in the example.

[0041] Figure 4 This is a SEM backscattered electron image of the longitudinal section of the degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared in the example after rolling for 10 times.

[0042] Figure 5 This is a SEM backscattered electron image of the cross section of the degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared in the example after rolling for 10 times. DETAILED DESCRIPTION

[0043] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0044] Example 1 (zinc powder filled into iron foam: magnesium powder = 4:1) The iron foam bracket was pickled with oxalic acid solution and dried immediately. Then, a round stainless steel brush with a wire diameter of 0.3 mm was used to polish the contact surface of the Zn plate (1.5 mm) and the iron foam (2 mm) with a pore size of 80-110 ppi in parallel to the rolling direction to remove surface oxides and impurities. The polished Zn plate was placed in acetone for ultrasonic cleaning for 5 minutes to remove residual powder and other impurities. Zinc powder and magnesium powder with a particle size of 25 μm were mixed in a mass ratio of 4:1. After completion, the mixed zinc powder and magnesium powder filled the iron foam to obtain a filled foam, and then two Zn plates were used to cover the iron foam from top to bottom to obtain a composite plate (zinc plate: iron bracket = 9:1), (the mass fraction of magnesium powder in the composite plate is 1%) and fixed with copper wire to prevent the strips from sliding against each other. Then, a single pass cold rolling is performed using a two-roll rolling mill, and the deformation of the single pass cold rolling is controlled to be 70%. Then, the cold-rolled plate is cut into two pieces from the middle, stacked, and then single-pass cold rolling is performed. The cutting-stacking-single-pass cold rolling is repeated 10 times. During the repeated process, the deformation of the single pass cold rolling is 50%-60%, and the composite plate with a thickness of 1.2 mm is rolled. The present invention does not require any lubricant treatment, and repeated cold rolling completes the preparation of the final degradable Zn / Fe / Mg composite material.

[0045] Specific data Figure 1 This is a schematic diagram of the preparation of the cold-rolled sheet of the degradable iron skeleton reinforced Zn / Fe / Mg composite material in Example 1. Figure 2 The XRD pattern of the degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared in the embodiment after rolling 10 times. Figure 2 It can be concluded that magnesium-zinc phase and zinc-iron phase are generated during the rolling process.

[0046] Figure 3The tensile stress-strain curve and corresponding tensile performance data of the degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared in Example 1. The tensile mechanical properties of the degradable iron skeleton reinforced Zn / Fe / Mg composite material after lamination rolling showed a significant improvement, and its tensile yield strength (YS), tensile ultimate strength (UTS), and elongation were 229MPa, 255MPa, and 5.5%, respectively. The composite material showed obvious work hardening characteristics.

[0047] Figure 4 This is a SEM backscattered electron image of the longitudinal section of the degradable Zn / Fe / Mg composite material prepared in Example 1 after 10 passes of rolling. Figure 4 It can be seen that after lamination rolling, the longitudinal section of the degradable iron skeleton reinforced Zn / Fe / Mg composite material is layered, with the main body consisting of strip-shaped light gray zinc layers, dark gray leaf-shaped iron phases alternately interspersed with layered distribution characteristics, and small black particles of magnesium phase dispersed in it.

[0048] Figure 5 This is a SEM backscattered electron image of the cross section of the degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared in Example 1 after 10 rolling passes. It is composed of a light gray zinc phase, a dark gray iron support and a black magnesium phase. The enlarged part of the iron support can be seen in the figure.

[0049] Example 2 (zinc powder filled into iron foam: magnesium powder = 2:1) The iron foam bracket was pickled with oxalic acid solution and dried immediately. Then, a round stainless steel brush with a wire diameter of 0.3 mm was used to polish the contact surface between the Zn plate (1.5 mm) and the iron foam (2 mm) parallel to the rolling direction to remove surface oxides and impurities. The polished Zn plate was ultrasonically cleaned in acetone for 5 minutes to remove residual powder and other impurities. Zinc powder and magnesium powder with a particle size of 25 μm were mixed in a mass ratio of 2:1. After completion, the iron foam was filled with the mixed zinc powder and magnesium powder, and then the iron foam was covered with two Zn plates from top to bottom to obtain a composite plate (zinc plate: iron bracket = 9:1), and copper wire was used to perforate and fix to prevent the strips from sliding against each other. Then, a two-roller rolling mill is used for single-pass cold rolling, and the deformation of the single-pass cold rolling is controlled to be 70%. Then, the cold-rolled plate is cut into two pieces from the middle, stacked, and then single-pass cold rolling is performed. The cutting-stacking-single-pass cold rolling is repeated 10 times. During the repeated process, the deformation of the single-pass cold rolling is 50%-60%, and the composite plate with a thickness of 1.2 mm is rolled. The present invention does not require any lubricant treatment, and repeated cold rolling completes the preparation of the final degradable iron skeleton reinforced Zn / Fe / Mg composite material.

[0050] In the degradable iron skeleton reinforced Zn / Fe / Mg composite material provided in this example, the ratio of zinc powder to magnesium powder filled into the iron foam is 2:1.

[0051] Implementation Effect The SEM image in Example 2 shows that after lamination rolling, the longitudinal section of the degradable iron skeleton reinforced Zn / Fe / Mg composite material is layered, with a strip-shaped light gray zinc layer as the main body, dark gray leaf-shaped iron phases alternately interspersed therein and having a layered distribution characteristic, and small black granular magnesium phases dispersed therein.

[0052] Comparative Example 1 The iron foam support was pickled with oxalic acid solution and dried immediately. Then, a round stainless steel brush with a wire diameter of 0.3 mm was used to polish the contact surface between the Zn plate and the iron foam parallel to the rolling direction to remove surface oxides and impurities. The polished Zn plate was placed in acetone for ultrasonic cleaning for 5 minutes to remove residual powder and other impurities. After completion, the iron foam was filled with zinc powder and magnesium powder mixed in a certain proportion, and then two Zn plates were used to cover the iron foam up and down to obtain a composite plate (adjust the zinc plate: iron support = 5:1), and the copper wire was used to perforate and fix to prevent the strips from sliding against each other. Then, a single-pass cold rolling was performed with a two-roll mill, and the deformation of the single-pass cold rolling was controlled to be 70%. Then, the cold-rolled plate was cut into two pieces from the middle, stacked, and then single-pass cold rolling was performed. The cutting-stacking-single-pass cold rolling was repeated. During the repeated process, the deformation of the single-pass cold rolling was 50%-60%, and the composite plate with a thickness of 1.2 mm was rolled. The present invention does not require any lubricant treatment, and repeated cold rolling can complete the preparation of the final degradable iron skeleton reinforced Zn / Fe / Mg composite material. Other conditions are the same as those in Example 1, except that the ratio of zinc plate to iron support is adjusted to 5:1. When cold rolling is repeated for 8 times, severe cracking occurs and it is impossible to continue.

[0053] Comparative Example 2 The iron foam support was pickled with oxalic acid solution and dried immediately, and then a round stainless steel brush with a wire diameter of 0.3 mm was used to polish the contact surface between the Zn plate and the iron foam parallel to the rolling direction to remove surface oxides and impurities. The polished Zn plate was placed in acetone for ultrasonic cleaning for 5 minutes to remove residual powder and other impurities. After completion, the iron foam was filled with the same mass of magnesium powder in Example 2, and then the iron foam was covered with two Zn plates up and down to obtain a composite plate (zinc plate: iron support = 9: 1), and fixed with copper wire perforations to prevent the strips from sliding against each other. Then, a single-pass cold rolling was performed with a two-roll mill, and the deformation of the single-pass cold rolling was controlled to be 70%. Then, the cold-rolled plate was cut into two pieces from the middle, stacked, and then single-pass cold rolling was performed. The cutting-stacking-single-pass cold rolling was repeated 10 times. During the repeated process, the deformation of the single-pass cold rolling was 50%-60%, and the composite plate with a thickness of 1.2 mm was rolled. The present invention does not require any lubricant treatment, and repeated cold rolling completes the preparation of the final degradable iron skeleton reinforced Zn / Fe / Mg composite material. The other conditions are the same as those in Example 2, except that the zinc powder in the mixed zinc powder and magnesium powder used to fill the iron foam in Example 2 is removed, and only magnesium powder is used for filling. Characterization of the finally prepared Zn / Fe / Mg composite material revealed that there were many holes, which affected its mechanical properties and resulted in poor tensile properties.

Claims

1. A method for preparing a degradable iron skeleton reinforced Zn / Fe / Mg composite material, characterized in that: Zinc powder and magnesium powder are mixed to obtain a mixed powder, and the iron foam is filled with the mixed powder. The iron foam is then covered with two Zn plates from top to bottom to obtain a composite plate. The composite plate is subjected to a single-pass cold rolling to obtain a cold-rolled plate. The cold-rolled plate is cut into two pieces from the middle, stacked, and then subjected to a single-pass cold rolling. The cutting-stacking-single-pass cold rolling process is repeated to finally obtain a degradable Zn / Fe / Mg layered composite material.

2. The method for preparing a degradable iron skeleton reinforced Zn / Fe / Mg composite material according to claim 1, characterized in that: The particle size of the zinc powder and magnesium powder is 20-40 μm, and the purity is ≥ 99.9%; In the mixed powder, the mass ratio of zinc powder to magnesium powder is 1-5:

1.

3. The method for preparing a degradable iron skeleton reinforced Zn / Fe / Mg composite material according to claim 1, characterized in that: The pore size of the Fe foam is 80-110 ppi; The purity of the Fe foam is ≥99.9%; The thickness of the Fe foam is 1.5-2.5 mm.

4. The method for preparing a degradable iron skeleton reinforced Zn / Fe / Mg composite material according to claim 1, characterized in that: The thickness of the Zn plate is 0.8-1.5 mm.

5. The method for preparing a degradable iron skeleton reinforced Zn / Fe / Mg composite material according to claim 1, characterized in that: The mass ratio of the Zn plate to the iron foam is 6-10:

1.

6. A method for preparing a degradable iron skeleton reinforced Zn / Fe / Mg composite material according to any one of claims 1 to 5, characterized in that: The deformation of the composite plate in a single cold rolling is 60%-70%.

7. A method for preparing a degradable iron skeleton reinforced Zn / Fe / Mg composite material according to any one of claims 1 to 5, characterized in that: The cold-rolled plate is cut into two pieces from the middle, stacked, and then single-pass cold-rolled. In the process of repeated cutting-stacking-single-pass cold-rolling, the deformation amount of any single-pass cold-rolling is controlled to be 50%-60%.

8. A method for preparing a degradable iron skeleton reinforced Zn / Fe / Mg composite material according to any one of claims 1 to 5, characterized in that: The number of repeated cutting-lamination-single-pass cold rolling is 2-10 times.

9. The degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The degradable iron skeleton reinforced Zn / Fe / Mg composite material is mainly composed of strip-shaped light grey zinc layers, dark grey leaf-shaped iron phases are alternately interspersed therein and have a layered distribution, and black granular magnesium phases are dispersed therein.

10. Application of the degradable iron skeleton reinforced Zn / Fe / Mg composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The degradable iron skeleton reinforced Zn / Fe / Mg composite material is used for biodegradable implant material.

Citation Information

Patent Citations

  • Preparation method of multilayer structural porous metal / nano carbon phase composite material

    CN106735247A

  • Biodegradable medical magnesium alloy repairing patch as well as preparation method and application thereof

    CN108853608A

  • Method for making semifinished products of light-weight energy- and sound- absorbing heat insulation material

    RU2205726C1

  • Method For Manufacturing A Metal Assembly

    US20130022834A1